Sibilant [s] Phonological Study : Sibilant [s] Sound in Preschool Children 4 Years 7 Months Age: BUNYI SIBILAN [s] PADA ANAK PRASEKOLAH USIA 4 TAHUN 7 BULAN - Hilyati Firdaus, Shabrina (Jurnal Pena Indonesia, 2024)
The sibilant sound is a language sound produced by rubbing the tongue against the tip of the teeth or gums. Sibilant sound is an important sound in language, because it can distinguish the meaning of a word or phrase. The development of sibilant sounds in children usually starts from the age of 3 years, with the existence of this study conducted with the aim of describing the sibilant [s] sound in preschool children at the age of 4 years and 7 months with male gender and using Indonesian colloquial language. Through the case study approach method by fishing for words containing sibilant [s] letters using toys or foods that are familiar in the research subject's environment. The results showed that A has not been able to pronounce the sibilant [s] sound even though he is 4 years and 7 months old and naturally replaces the role of sibilant [s] consonants with [c], [t], [k] consonants caused by the family environment not focusing their attention on developing word pronunciation during simple interactions.